Pengaruh Pemanfaatan Tanaman Pembatas Pinggiran Terhadap Populasi Hama dan Musuh Alami Pada Pertanaman Kubis (Brassica Oleracea L.) - SIROJUDDIN, MIFTAHUS; YULIADHI, KETUT AYU; WIDANINGSIH, DWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Effect of Plant Utilization Limiting Fringe Against Population Pests and Natural Enemies On Planting Cabbage ( Brassica oleracea l .)   The purpose of the study is  to determine the effect of plant utilization Limiting Fringe barrier against pest species diversity, species diversity of natural enemies, pest species abundance, and abundance of natural enemy species on cabbage crop. The research was conducted in two places items, namely in the field and in the laboratory. Sampling is done diagonally plant. Pest species diversity on both compartments consisting of six species of Aphis brassicae , Crocidolomia pavonana Fab, Plutella xylostella L, Spodoptera litura Fab, Helicoverpa armigera Hubner, and Chrysodeixis orichalcea . There are three species that have a more dominant population abundance namely A. brassicae, P. xylostella and C. pavonana . Species diversity of natural enemies of equal treatment, both in the parasitoid diversity consists of a single species Diadegma semiclausum .e. whereas in the diversity of the species there are six predator Menochilus sexmaculatus , Ischiodon scutellaris , Paederus fuscipes Curt, Dolichoderus bituberculatus , Oecophylla smaragdina and Sycanus sp. The results Showed an Increase in the percentage of the natural enemies of the moment map of plant cabbages planted with crops in the suburban area of the Cabbage Cropping.
Keywords: Natural Enemies; Cabbage; Pest